CFD Simulation for Brake Resistor of Rail Vehicle - DING Jie; TANG Yu-tu (机车电传动)
In order to analyze the distribution of surface temperature, velocity and pressure field on the brake resistance chip in the process of rail vehicle’s resistance brake, simulation model of brake resistance chips was established by considering the influence of the temperature on thermal physical property parameters of the air. The results showed that CFD simulation was useful for the design of brake resistor.